2011
DOI: 10.1259/bjr/16007764
|View full text |Cite
|
Sign up to set email alerts
|

Enterolith ileus: liberated large jejunal diverticulum enterolith causing small bowel obstruction in the setting of jejunal diverticulitis

Abstract: ABSTRACT. We present an 80-year-old man with multiple medical problems, and acute abdominal pain with feculent emesis. An unenhanced CT examination of the abdomen and pelvis demonstrated jejunal diverticulitis and findings of high-grade small bowel obstruction caused by a large enterolith. Enterolith ileus has rarely been reported in the radiology literature. This phenomenon has occasionally been reported in the surgical and gastroenterology literature. We highlight the CT findings associated with enterolith i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Even fewer describe acute small bowel obstruction due to an impacted enterolith 1. In authors knowledge, we found three similar cases where patients presented with coexisting jejunal diverticulitis with a dislodged enterolith causing acute small bowel obstruction 1–3…”
Section: Discussionmentioning
confidence: 81%
“…Even fewer describe acute small bowel obstruction due to an impacted enterolith 1. In authors knowledge, we found three similar cases where patients presented with coexisting jejunal diverticulitis with a dislodged enterolith causing acute small bowel obstruction 1–3…”
Section: Discussionmentioning
confidence: 81%
“…From a review of these case reports, enteroliths seemingly have a preponderance to cause obstruction in the mid-jejunum 3 5 6. However, there are reports of enteroliths causing obstruction in the distal jejunum7 and mid-small bowel 8…”
Section: Discussionmentioning
confidence: 99%
“…Diverticulosis of the small bowel is rare, being found in less than 5% of patients at post‐mortem examinations, and is thought to arise as a result of bowel dyskinesia, abnormal peristalsis or high intraluminal pressures . It occurs more frequently in men in their 60s and 70s .…”
mentioning
confidence: 99%
“…It occurs more frequently in men in their 60s and 70s . Small bowel diverticulae occur most commonly in the duodenum (60–70%), followed by the jejunum (20–25%) and the ileum (5–10%), and are usually found on the mesenteric border of the small bowel at the site of insertion of mesenteric vessels . They are usually found incidentally either during endoscopy, on imaging or at the time of operation .…”
mentioning
confidence: 99%
See 1 more Smart Citation